Induced membrane technique using bone cement with or without cefazolin in chicken segmental radius defect - Campeiro Junior, Luiz D.; Rahal, Sheila Canevese; Souza, Marcos A.; Osowski, Alini; Silva Júnior, José I. S. (Frontiers in Veterinary Science, 2023)
The utilization of antibiotic-loaded cement spacer in the induced membrane development has been a debate topic in human medicine. To the best of the author's knowledge, these combinations have not yet been evaluated in birds. Therefore, this study assessed induced membrane formation using radiography and histology, in a segmental defect of a chicken radius, with or without the addition of cefazolin. Thirty 18-month-old healthy chickens were divided into two equal groups: G1—bone defect filled with bone cement; G2—bone defect filled with cefazolin powder-loaded bone cement. Radiographic examinations of the left forearm were taken immediately after surgery and at 7, 15, and 21 postoperative days. For the collection of the induced membranes, five chickens in each group were euthanized at 7, 15, and 21 days after surgery. Radiographically, the bone cement was identified as a radiopaque structure occupying the bone defect in both groups. Mild new bone formation in at least one of the fractured extremities of the bone defect was seen only 21 days after surgery in most chickens. Histologically, there was no difference in the mean thickness of the induced membrane between groups at all time points. Multifocal multinucleated cells differed between groups at 7 (G1 > G2) and 21 (G2 > G1) days after surgery. Mononuclear inflammatory infiltrate differed between groups only on day 21 (G1 > G2). Fibrous tissue proliferation did not differ between groups at all evaluation times. Blood vessel density differed only at 21 days postoperatively (G2 < G1). Multifocal areas of cartilage differed between groups at all time points (G1 > G2). In conclusion, cefazolin mixed with bone cement did not affect thickness of the induced membrane, but did result in a negative effect on some histological aspects, such as fewer vessels, less multifocal areas of cartilage, and persistence of inflammation.